Inter-Multidisciplinary Islamic Scholarship: Contributions to Tolerance and Intercultural Harmony - Sigit Barazili; M Nasor (EDUCATIO : Journal of Education, 2024)
A broad and deep understanding of Islam in the contemporary context has become increasingly important for promoting tolerance and intercultural harmony around the world. One of the emerging approaches in Islamic studies is inter/multidisciplinary scholarship, which allows the integration of various disciplines to explore this aspect of the religion holistically. This paper discusses the contribution of inter/multidisciplinary Islamic scholarship in strengthening tolerance and intercultural harmony. This approach helps individuals understand Islam in a broader framework, reduce religious prejudice, and promote constructive intercultural dialog. Through these studies, we can better embrace religious diversity and work towards a more inclusive and just society. In addition, inter/multidisciplinary Islamic scholarship has the potential to advance the understanding of how Islam contributes to global peace and the resolution of contemporary issues. In an increasingly connected world, understanding the religion with a holistic approach is an important step in creating a more tolerant and harmonious society.